Secured Hardware Accelerators for DSP and Image Processing Applications - Sengupta, Anirban (Computer scientist) (Materials, circuits and devices series, 2020)
This book presents state-of-the art security solutions and optimization algorithms employed for designing secured hardware accelerators for DSP, multimedia and image processing applications. Broadly, the theme of this book includes the following: secured and optimized hardware accelerators for DSP and image processing applications; cryptography-driven IP steganography for DSP hardware accelerators; double line of defence to secure JPEG codec hardware for medical imaging systems; integrating multi-key-based structural obfuscation and low-level watermarking for double line of defence of DSP hardware accelerators; multimodal hardware accelerators for image processing filters; fingerprint biometric for securing hardware accelerators; key-triggered hash-chaining-based encoded hardware steganography for securing DSP hardware accelerators; N-point DFT hardware accelerator design using obfuscation and steganography; and structural transformation and obfuscation frameworks for data-intensive IPs.